Prognostic Utility of Left Ventricular Ejection Fraction in Patients Undergoing Transcatheter Aortic Valve Implantation ― A Systematic Review and Meta-Analysis - Nabeshima, Yosuke; Kitano, Tetsuji; Sakamoto, Yoshiko; Takeuchi, Masaaki; Node, Koichi (Circulation Reports, 2025)
Background: Left ventricular ejection fraction (LVEF) is widely used to assess systolic function and to predict cardiovascular outcomes, but its prognostic role in patients undergoing transcatheter aortic valve implantation (TAVI) remains uncertain.Methods and Results: We performed a systematic review and meta-analysis of studies published from 2001 to 2024 that evaluated the association between preprocedural LVEF and post-TAVI outcomes. Eligible studies were identified via PubMed and Scopus, and included those reporting hazard ratios for preprocedural LVEF. A total of 92 studies comprising 98 patient cohorts and 75,085 individuals were included. Random-effects models were used for univariable and multivariable analyses. Subgroup and meta-regression analyses assessed effect modifiers, including ethnicity, LVEF classification, endpoints, and study design. Each 1% decrease in LVEF was associated with an increased risk of adverse events (hazard ratio 1.02, 95% confidence interval: 1.01–1.03), and this association remained significant after adjusting for confounders. Subgroup analyses confirmed the robustness of this association in various settings. In the multivariable meta-regression, studies with lower mean LVEF demonstrated a stronger association between reduced LVEF and adverse outcomes, but this association was attenuated or nonsignificant in cohorts with preserved systolic function. This suggests that the prognostic value of LVEF may depend on the baseline level of ventricular function and is subject to effect modification.Conclusions: Reduced preprocedural LVEF is independently associated with worse prognosis after TAVI. These results highlight the continued importance of LVEF in risk stratification and clinical decision-making in TAVI candidates.